Penerapan Media Benda Konkrit Untuk Meningkatkan Hasil Bela-jar Matematika Peserta Didik Kelas 1A SD Negeri 219 Bengkulu Utara - Ritamah, Ritamah (Yayasan Darussalam Bengkulu, 2020)
This research is a Classroom Action Research (CAR) which aims to improve the learning outcomes of class I A students of SD Negeri 219 Bengkulu Utara. The research was carried out in 2 cycles, each cycle consisting of 4 stages, namely planning, implementing the action, observing and reflecting. The time for conducting the research starts from July 2019 to March 2020 with an agenda from planning to preparing reports. Meanwhile, the research site was conducted at SD Negeri 219 Bengkulu Utara. The results of the research on the Application of Concrete Object Media to Improve the Learning Outcomes of Class 1 A Students of SD Negeri 219 Bengkulu Utara for the 2019/2020 academic year can improve learning outcomes. This can be seen from the increasing percentage of students who have completed it. The learning outcomes of students in the complete cycle I reached 34.4%, while in cycle II students who completed reached 86.2%, there was an increase of 51.8%.